1973
DOI: 10.1159/000230945
|View full text |Cite
|
Sign up to set email alerts
|

Two Classes of Homocytotropic Antibodies in the Rhesus Monkey

Abstract: Rhesus monkeys injected intravenously with TNP-KLH produced homocytotropic antibody separable into two components on ion exchange chromatography, a heat-labile γ1- and a heat-stable γ2-immunoglobulin. Homocytotropic antibody was directed against the TNP group only, though both groups of determinants gave rise to large amounts of precipitating antibody. Arthus reactions induced by TNP on heterologous carrier were more severe than those caused by KLH. Prolonged TNP-induced reactions resembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1974
1974
1980
1980

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A number of immunologic similarities between the monkey and man suggest that monkeys could serve as a useful model for the investigation of human hypersensitivity. As in man (PARISH 1974), anaphylactic antibodies belonging to the IgE and IgG classes have been identified ( AMKRAUT et al 1973), and different models of systemic anaphylaxis have been worked out in the monkey using active (KOPELOFF & KOPELOFF 1938, PARISH et al 1966 or passive sensitization (LAYTON & GREENE 1964, PATTERSON et al 1966. All that is known about cardiorespiratory function, however, is that an allergen may induce systemic hypotension, sometimes accompanied by pulmonary hypertension (PATTER- SON et al 1966).…”
mentioning
confidence: 99%
“…A number of immunologic similarities between the monkey and man suggest that monkeys could serve as a useful model for the investigation of human hypersensitivity. As in man (PARISH 1974), anaphylactic antibodies belonging to the IgE and IgG classes have been identified ( AMKRAUT et al 1973), and different models of systemic anaphylaxis have been worked out in the monkey using active (KOPELOFF & KOPELOFF 1938, PARISH et al 1966 or passive sensitization (LAYTON & GREENE 1964, PATTERSON et al 1966. All that is known about cardiorespiratory function, however, is that an allergen may induce systemic hypotension, sometimes accompanied by pulmonary hypertension (PATTER- SON et al 1966).…”
mentioning
confidence: 99%
“…IgG homocyto tropic antibodies have been demonstrated in guinea pigs [31], mice [29], rats [28], and rhesus monkeys [32]. The reported heterogeneity of homocytotropic antibodies in various animal species together with the observa tions reported in this paper would suggest that human reaginic antibody may not be a unique immunoglobulin.…”
Section: Discussionmentioning
confidence: 47%
“…Since no antibodies of the IgE class were detectable, this reaction could be clas sified as aggregate anaphylaxis [4]. It has been reported that homocytotropic antibod ies of the IgG class may appear in the mon key [1] and in man [24], It is not known whether ovalbumin-specific homocytotropic IgG was of any significance in the present study. When antigen-antibody complexes preformed in vitro (mainly IgG) were inject ed into unsensitized monkeys, most of the symptoms of aggregate anaphylaxis ob served in actively sensitized monkeys were produced [Smedegárd, unpubl.…”
Section: Discussionmentioning
confidence: 71%